Histopathological pattern of primary ovarian neoplasms in South Western Nigeria. (2016)
Background: Ovarian tumours are common form s o f neoplasms in women. This study aims to determine the histopathological pattern o f primary ovarian neoplasms in South-western Nigeria. Method: A retrospective study was undertaken to review the histopathology reports o f all primary ovarian neoplasm specimens submitted to the Department o f Pathology, University College Hospital, Ibadan from January 1991 to June 2013. Patients'biodata were extractedfrom the requestforms and surgical day books. Results: There were 821 cases o f primary ovarian neoplasms. 359 (43.7%) cases were surface epithelial neoplasms which were found in patients with age range 10-89 years. Three hundred and thirteen (38%) cases o f germ cell tumour were found in patients with age range 0-70 years. One hundred andforty-six (17.8%) cases ofsex cord stromal tumour werefound in patients with age range 0-99 years. Mature Cystic Teratoma was the most common (54.7%) among benign ovarian neoplasms with 20-29 years being the age range with highest tumours while serous cystadenocarcinoma was the most common (33.2%) primary malignant ovarian neoplasms with 50-59years being the age range with highest tumours. Conclusion: Surface epithelial tumours were the most common ovarian neoplasmfollowed by germ cell tumours. This pattern is observed in most parts of Nigeria, some African and Asian countries, and in the Western world.